Efeitos hipotensivo e diurético dos extratos aquosos de pitanga (Eugenia uniflora L.) e jambolão (Eugenia jambolana Lam.) em ratos normotensos anestesiados - Cirqueira, R. T.; Alves, M. J Q F [UNESP] (My University, 2005)
Plants that possess a diuretic effect are widely used by people in the treatment of some important diseases as edema and hypertension. The objective of this work was to study the effects of pitanga and jambos aqueous extracts (AE) about the arterial pressure (AP) and urinary flow (V) in normotensive and anesthetized rats. The AE were prepared for the decoction method and administrated for intragastric way in different concentrations: 10%, 15%, 20% and 25%. These concentrations corresponded respectively at doses of 56, 94, 145, 172 mg of pitanga dried extract /Kg and 44, 73, 83, 95 mg of jambos dried extract/Kg. The animals were divided in nine groups with seven individuals (n=7): control (C), P-10%, P-15%, P-20%, P-25%, J-10%, J-15%, J-20% and J-25%. The rats were anesthetized (hypnol 3%) and submitted to tracheotomy. The left carotide artery was catheterized to measure the AP through a mercury manometer, in periods of 15 minutes. The bladder was catheterized for urine collection and to measure the V, in periods of 30 minutes. The experimental protocol was divided in four periods of 30 minutes each: basal (to evaluate of the basal parameters) and experimental (Exp) 1, 2 and 3 (after the administration of the AE). The results were analyzed for ANOVA and Tukey (X±SD, p<0.05). In the C group did have not alteration of the AP basal but the V basal increased. In the experimental groups (AE of P and J) had significative decline in the AP basal: 34% (P-10%), 20% (P-15%), 21% (P-20%), 31% (P-25%), 24% (J-10%), 20% (J-15%) 16% (J-20%) and 29% (J-25%). Moreover, the administration of AE increased the V basal in: 280% (P-15%) and 192% (J-20%). The results showed that the plants evaluated are hypotensive and diuretic.
Hypotensive and diuretic effects of pitanga (Eugenia uniflora L.) and jambos (Eugenia jambolana Lam.) aqueous extracts in normotensive anesthetized rats
Keywords: Diuretic; Hypotensive; Jambos; Medicinal plants; Pitanga; Eugenia uniflora extract; plant extract; Syzygium cumini extract; unclassified drug; animal experiment; antihypertensive activity; arterial pressure; controlled study; diuresis; diuretic activity; Eugenia; eugenia jambolana; eugenia uniflora; medicinal plant; micturition; nonhuman; rat; Animalia; Eugenia uniflora; Syzygium cumini